2021
DOI: 10.1016/j.jobcr.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic approaches of microRNAs for COVID-19: Challenges and opportunities

Abstract: The coronavirus disease 2019 (COVID-19) emerges as current outbreak cause by Novel Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2). This infection affects respiratory system and provides uncontrolled systemic inflammatory response as cytokine storm. The main concern about SARS-CoV-2 pandemic is high viral pathogenicity with no specific drugs. MicroRNAs (miRs) as small non-coding RNAs (21–25 nt) regulate gene expression. The SARS-CoV-2 encoded-miRs affect human genes that involved in transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…The COVID‐19‐encoded miRNAs as autocrine or paracrine agonists of host cells increased nuclear factor kappa B activity and stimulated proinflammatory cytokines (Arisan et al, 2020 ). Therefore, further investigation is required to identify specific miRNAs that target and stop virus‐induced infection (Farshbaf et al, 2020 ; Pontecorvi et al, 2020 ).…”
Section: Limitations Of Mirnas Against Covid‐19mentioning
confidence: 99%
“…The COVID‐19‐encoded miRNAs as autocrine or paracrine agonists of host cells increased nuclear factor kappa B activity and stimulated proinflammatory cytokines (Arisan et al, 2020 ). Therefore, further investigation is required to identify specific miRNAs that target and stop virus‐induced infection (Farshbaf et al, 2020 ; Pontecorvi et al, 2020 ).…”
Section: Limitations Of Mirnas Against Covid‐19mentioning
confidence: 99%
“…SARS-CoV-2 encoded miRNAs alter host gene expression to create a favorable environment for viral infection. Interestingly, host miRNAs can play dual roles as both antiviral and proviral factors [ 45 ]. The number of host miRNAs targeting the SARS-CoV-2 genome sequence inhibits viral replication by regulating innate antiviral immunity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aydemir et al have identified 20 pre-miRNA candidates and 40 mature miRNAs encoded by SARS-CoV-2, which can regulate host gene expression by targeting NFKB, JAK/STAT, and TGFB signaling pathways [ 44 ] ( Table 2 ). Therefore, viral miRNAs, such as SARS-CoV-mir-D8- 5p and SARS-CoV-mir-R1-5p, target many human genes involved in the transcription, metabolism, and immune systems, implicating the roles of miRNAs during viral infection [ 44 , 45 ]. Likewise, predicted 26 mature miRNAs from the SARS-CoV-2 genome might target human genes involved in innate antiviral immunity [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar DNA lengths are commonly exploited for PCR primers, or in structural DNA-nanotechnology applications [26]. Moreover, 23 bases represents the average length of micro-RNA (miRNA) biomarkers, a class of naturally occurring, small, noncoding RNA molecules, which are the target of several microarrays or biosensors [23,27]. The sequence of the surface-immobilized probe was: 5 -GCCCACCTATAAGGTAAAAGTGA-3 .…”
Section: Dna Strands and Reagentsmentioning
confidence: 99%